Thermal radiation, Newtonian heating, Hall and ion slip effects on unsteady MHD rotating convective flow of Casson fluid past an infinite smooth vertical porous surface - M. Veera Krishna; B.V. Swarnalathamma; K. Bharathi (Results in Engineering)
In the current paper, the impacts of the Newtonian heating on the heat and mass transportation in unsteady MHD flow of the Casson fluid past an infinite vertical plate by means of thermal radiation and chemical reaction are investigated with Hall and ion slip effects. The Casson fluid model is utilizing to distinctive the non-Newtonian fluid performance. The fluid flow is convinced suitable to periodic oscillations with the plate next to this length and the uniform transverse magnetic field is abounding to the direction, it is perpendicular to the direction of the fluid movement. The partial differential equations for the governing flow momentum, temperature, and mass transportation are converted into a non-dimensional form using the appropriated non-dimensional variables. Then these are later solved systematically making use of Laplace transformation technique. The current computational quantities namely, the fluid velocity, temperature, and species concentration are portraying with graphical profiles. In addition, the skin-friction, Nusselts number, and Sherwood numbers are presented in the tabular format with respect to the non-dimensional parameters. Therefore, it is noticed that, the fluid velocity and the temperature are reducing with growing in Casson parameter while the concentration field is reducing with an increasing in chemical reaction parameter and Schmidt number. Therefore, the fluid flow model has quite the lot of engineering and medicinal applications these are, in glass manufactures, paper production, and purification of crude oils and investigation of the blood flow in the cardio-vascular systems.